Enhancement of biogas production from sewage sludge by biofilm pretreatment method - Bouh, Ibrahim Gamiye; Alam, Md. Zahangir; Kabbashi, Nassereldeen Ahmed (Kulliyyah of Engineering, International Islamic University Malaysia, 2018)
Since the last two decades, different pre-treatment methods have been proposed to enhance the yield of biogas production from sewage sludge. In order to improve the biogas yield and to find an alternative and economically suitable pretreatment method, a biological pretreatment method using a biofilm was studied. The biofilm constituted of four strains of bacteria producing hydrolyzes was used as an immobilized biocatalyst for the pretreatment of the sludge. Based on the data obtained during this study, the optimum biofilm was formed within 2 days. The best amount of GAC that has given an optimum biofilm was 4g. An improvement of 16.9% on the SCOD/TCOD and 28.3% in the volatile solids (VS) was achieved after 12 hours of pretreatment at room temperature (30 ± 2⁰C). Comparing to the no pretreated sludge (control), 15% of an increase in the cumulative biogas production was observed after 14 days of digestion with 30% v/v of inoculum (anaerobic sludge) at 37⁰C and 25 days of HRT. It can be concluded that the developed pretreatment method can be used for the enhancement of the biogas production from sewage sludge at mesophilic temperature range.